Development of Conflict Management Style Media Development Based on Android to Know the Style of Managing Conflict of High School Students - Qorina Aris Budiarti; Retno Tri Hariastuti; Endang Pudjiastuti Sartinah (IJORER : International Journal of Recent Educational Research, 2022)
This study aims to develop a set of android CMS (Conflict Management Style) to find out the style of managing conflict among high school students as an important information to reduce conflict appropriately and responsibly that meets the assessment criteria of acceptability includes aspects of usability, feasibility, accuracy and propriety. This research uses the Borg & Gall development research method which includes: (1) preliminary studies; (2) planning; (3) initial product development; (4) testing expert validation; (5) product revision. After that, the data were analyzed using quantitative and qualitative methods. The material expert test assessment shows 92.19%, means that the contents of CMS (Conflict Management Style) android material is very good, no revision needed. Not only that, the Rating media expert test also shows a very good results, which is 100%, it means that this application design can be considered as a very good one. So concluded that the development of android-based conflict management style understanding media to determine students' conflict management styles had met the criteria for good acceptability in the design and content of the discussion, so that the Android CMS (Conflict Management Style) could be used as information to reduce and direct conflict.